2013
DOI: 10.1007/s11207-013-0447-9
|View full text |Cite
|
Sign up to set email alerts
|

The Ten-Rotation Quasi-periodicity in Sunspot Areas

Abstract: Sunspot-area fluctuations over an epoch of 12 solar cycles (12 -23) are investigated in detail using wavelets. Getko (Universal Heliophysical Processes, IAU Symp. 257, 169, 2009) found three significant quasi-periodicities at 10, 17, and 23 solar rotations, but two longer periods could be treated as subharmonics of the ten-rotation quasi-periodicity. Therefore we focused the analysis on the occurrence of this quasi-periodicity during the low-and high-activity periods of each solar cycle. Because of the N -S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…The slight offset between peaks in the low- (28 days) and high-latitude (30 days) period is consistent with observed solar differential rotation 24 . The broad peak centred around 330 days is common to the timeseries, although the southern hemisphere seems to be shifted further and is consistent with the analysis of Getko 25 26 . This appears to be the primary (quasi-)periodicity of the magnetic surges that shape the heliosphere and drive the host of energetic phenomena observed as described above.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The slight offset between peaks in the low- (28 days) and high-latitude (30 days) period is consistent with observed solar differential rotation 24 . The broad peak centred around 330 days is common to the timeseries, although the southern hemisphere seems to be shifted further and is consistent with the analysis of Getko 25 26 . This appears to be the primary (quasi-)periodicity of the magnetic surges that shape the heliosphere and drive the host of energetic phenomena observed as described above.…”
Section: Resultssupporting
confidence: 86%
“…Figure 7 permits a phenomenological explanation of the quasi-periodicities (of order 150 days) that have been observed in a large number of heliospheric quantities by Rieger and others 9 10 11 25 26 27 28 29 35 . Those are ‘hybrid' periodicities—a consequence of the phase relationship between the short-term variability in each solar hemisphere.…”
Section: Discussionmentioning
confidence: 78%
“…Getko (2008) found that the sunspot area fluctuations in the northern and the southern hemispheres show quasiperiodicity over 9 months. Moreover, the result of Getko (2014) reported that this period is mainly detected during the high-activity periods, which is the same as our results for the local wavelet spectra. It may reveal the special characteristics of partial-halo CMEs compared to other angular widths.…”
Section: Discussionsupporting
confidence: 91%